MR imaging for diagnostic evaluation of encephalopathy in the newborn. - Shroff, MM (2013)
Magnetic resonance (MR) imaging is used with increasing frequency to evaluate the neonatal brain because it can provide important diagnostic and prognostic information that is needed for optimal treatment and appropriate counseling. Special care must be taken in preparing encephalopathic neonates for an MR study, transporting them from the intensive care unit, monitoring their vital signs, and optimizing MR sequences and protocols. Moreover, to accurately interpret the findings, specific knowledge is needed about the normal MR imaging appearances of the physiologic processes of myelination, cell migration, and sulcation, as well as patterns of injury, in the neonatal brain at various stages of gestational development. Hypoxic-ischemic injury, the most common cause of neonatal encephalopathy, has characteristic appearances that depend on the severity and duration of the insult as well as the stage of brain development. Diffusion-weighted MR imaging and MR spectroscopy depict abnormalities earlier than do conventional MR imaging sequences. However, diffusion-weighted imaging, if performed in the first 24 hours after the insult, might lead to underestimation of the extent of injury. When the MR findings are atypical, the differential diagnosis of neonatal encephalopathy also should include congenital and metabolic disorders and infectious diseases. Despite recent advances in the MR imaging-based characterization of these conditions, the clinical history must be borne in mind to achieve an accurate diagnosis.